Managing cyclic vomiting syndrome in children: beyond the guidelines - Li, B U.K. (Eur J Pediatr, 2018)
Cyclic vomiting syndrome (CVS) in children is characterized by frequent hospitalizations, multiple comorbidities, and poor quality of life. In the absence of robust data, the treatment of CVS remains largely empiric starting with the 2008 NASPGHAN Consensus Statement recommendations of cyproheptadine for children < 5 years of age and amitriptyline for those ≥ 5 years with propranolol serving as the second-line agent. Comprehensive management begins with lifestyle alterations, and extends to medications, supplements, and stress reduction therapies. Standard drug therapy is organized by the four phases of the illness: (1) interictal (preventative medications and mitochondrial supplements), (2) prodromal (abortive agents), (3) vomiting (fluids/energy substrates, antiemetics, analgesics, and sedatives) and (4) recovery (supportive care and nutrition). Because the response to treatment is heterogeneous, clinicians often trial several different preventative strategies including NK1 antagonists, cautious titration of amitriptyline to higher doses, anticonvulsants, Ca(2+)-channel blockers, and other TCA antidepressants. When the child remains refractory to treatment, reconsideration of possible missed diagnoses and further mono- or combination therapy and psychotherapy can be guided by accompanying comorbidities (especially anxiety), specific subphenotype, and when available, genotype. For hospital intervention, IV fluids with 10% dextrose, antiemetics, and analgesics can lessen symptoms while effective sedation in some instances can truncate severe episodes. Conclusion: Although management of CVS remains challenging to the clinician, approaches based upon recent literature and accumulated experience with subgroups of patients has led to improved treatment of the refractory and hospitalized patient.